2003
DOI: 10.1097/00006982-200306000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Evaluation of Patients on Chronic Amiodarone Therapy

Abstract: No significant adverse retinal funduscopic changes or electrophysiologic effects could be correlated with amiodarone exposure in this small series of patients. Routine electrophysiologic and funduscopic screening of patients receiving amiodarone does not seem warranted, although future prospective controlled studies may be required to exclude the possibility of progressive abnormalities in patients with preexisting age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Shaikh et al performed mfERG in patients who had been on long-term amiodarone therapy to evaluate the potential retinal toxicity topographically. 278 It was shown that some patients had subnormal P1 amplitudes and mild prolongation in P1 implicit times. The authors believed that the mfERG changes were probably age-related or due to testing variability and further studies should be performed to determine the extent of retinal toxicity associated with long-term amiodarone therapy.…”
Section: Amiodaronementioning
confidence: 99%
“…Shaikh et al performed mfERG in patients who had been on long-term amiodarone therapy to evaluate the potential retinal toxicity topographically. 278 It was shown that some patients had subnormal P1 amplitudes and mild prolongation in P1 implicit times. The authors believed that the mfERG changes were probably age-related or due to testing variability and further studies should be performed to determine the extent of retinal toxicity associated with long-term amiodarone therapy.…”
Section: Amiodaronementioning
confidence: 99%
“…While a cause and effect relationship has not been proven in the literature, 10 we believe that retinal surgeons should be cautious when performing pars plana vitrectomy and membrane peel surgery on patients using amiodarone because of its potential photosensitizing effects. The possibility of retinal phototoxicity should be discussed with the patient pre-operatively and an attempt to minimize operative time, and exposure to light should be made.…”
Section: Discussionmentioning
confidence: 88%
“… 8 Previous studies have failed to show any retinal side effects of amiodarone in vivo. 9 , 10 In vitro studies have, however, demonstrated that RPE cells treated with amiodarone have decreased survival when exposed to UV radiation. 11 Therefore, given that amiodarone deposits are found in retinal pigment epithelial cells and ganglion cells, and that amiodarone has photosensitizing properties on the skin and in RPE cells in vitro, there is a theoretical risk of retinal phototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observation that several patients receiving amiodarone developed atypical pigmentary maculopathy, Shaikh et al [85] evaluated the mfERG responses of 11 patients on chronic amiodarone therapy in order to investigate whether there are any correlations between this drug and the retinal disease. mfERG P1 amplitudes were normal in all but 2 patients.…”
Section: Amiodarone Retinopathymentioning
confidence: 99%